PH PHENOMENON OF HIV AIDS AMONG ADOLESCENTS IN TULUNGAGUNG REGENCY: Koni Elfina Postgraduate Program, Institute of Health Sciences (IIK) Strada Indonesia konielfina@gmail.com - Burhan, Koni Elfina (Journal of Global Research in Public Health, 2021)
Adolescence is closely related to psychological development in the pubertal period and is accompanied by sexual development. Adolescence is an age that is experiencing increased vulnerability to various health risk threats, especially those related to sexual and reproductive health, including the increased threat from HIV/AIDS. In 2020 KPA Tulungagung noted that there were 48 adolescents aged 10-24 years infected with HIV AIDS. This study aims to determine the phenomenon of HIV AIDS in adolescents in Tulungagung Regency. Samples were taken by purposive sampling, from adolescents aged 15-24 years who were positively infected with HIV AIDS in Tulungagung Regency as many as 49 people. Triangulation was carried out with the Secretary of KPA Tulungagung who is also a psychologist who handles and assists ODHA. This research is qualitative with descriptive method. Data collection is done by in-depth interview technique. The results showed that the factors that caused the participants to fall into promiscuity were internal factors and external factors. The impact is physical, biological, social and psychological problems. As for the efforts to tackle HIV AIDS cases in adolescents, namely (1) Providing knowledge and increasing awareness about HIV AIDS to the community; (2) Involve family participation in HIV AIDS prevention; (3) administer ARVs regularly, and (4) screen for HIV infection. Keywords: Factors, Impact, HIV/AIDS Control Solution